2022
DOI: 10.3390/nano12040712
|View full text |Cite
|
Sign up to set email alerts
|

Photodetection Tuning with High Absorptivity Using Stacked 2D Heterostructure Films

Abstract: Graphene-based photodetection (PD) devices have been broadly studied for their broadband absorption, high carrier mobility, and mechanical flexibility. Owing to graphene’s low optical absorption, the research on graphene-based PD devices so far has relied on hybrid heterostructure devices to enhance photo-absorption. Designing a new generation of PD devices supported by silicon (Si) film is considered as an innovative technique for PD devices; Si film-based devices are typically utilized in optical communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Silicon devices are generally used in visual image sensors due to their distinct properties such as increased light absorption, larger carrier mobility, and classical CMOS integration. Designing an innovative PD device using Si film is considered a novel approach for image sensors (see Figure a) . Electronic and optoelectronic devices have been studied with rippled or wrinkled graphene, which revealed that an increase in ripple density of graphite nanostructures with the help of a supporting PDMS layer, the photoresponsivity also increased (see Figure b) .…”
Section: Technological Evolution Of Image Sensing: An Overview On Cur...mentioning
confidence: 99%
See 2 more Smart Citations
“…Silicon devices are generally used in visual image sensors due to their distinct properties such as increased light absorption, larger carrier mobility, and classical CMOS integration. Designing an innovative PD device using Si film is considered a novel approach for image sensors (see Figure a) . Electronic and optoelectronic devices have been studied with rippled or wrinkled graphene, which revealed that an increase in ripple density of graphite nanostructures with the help of a supporting PDMS layer, the photoresponsivity also increased (see Figure b) .…”
Section: Technological Evolution Of Image Sensing: An Overview On Cur...mentioning
confidence: 99%
“…Fabrication process of graphene-based photodetectors: (a) Fabrication process of Si/graphite film stacked layer photodetection devices. Reproduced with permission from ref . Copyright 2022 MDPI.…”
Section: Technological Evolution Of Image Sensing: An Overview On Cur...mentioning
confidence: 99%
See 1 more Smart Citation
“…11 It comprises a monolayer of carbon atoms arranged in a hexagon network. 7,18–42 Thus, graphene has been shown as a greatly promising material for future optoelectronic devices due to its remarkable features, including high mobility reaching up to 10 4 cm 2 V −1 s −1 at ambient temperature, exceptional thermal and electric conductivities, and ballistic transport. 12,43 Also, in the broad spectra range of visible and near-infrared (NIR), the transmittance of single layer graphene can reach 97.7%, and only 2.3% of the light intensity can be absorbed.…”
Section: Emergence Of Graphene/si In Solar Cells and Photovoltaicsmentioning
confidence: 99%
“…Since the successful isolation of graphene in 2004 by Novoselov et al , its unique physical properties have been extensively examined, garnering significant attention from the scientific community. 11–30 Due to its distinctive structure and extensive π-conjugation, graphene exhibits outstanding electrical and optical characteristics, positioning it as a promising candidate for applications in electronics and optoelectronics. 22,23,31–35 This has sparked a race to explore high-quality 2D materials and integrate them into semiconducting devices at economical prices.…”
Section: Introductionmentioning
confidence: 99%